Remembering Jo Cox (1974–2016). Issue 6 (1st November 2016) - Purvis, June
ABSTRACT: This appreciation remembers the life of Jo Cox, a British Member of Parliament (MP), who was brutally murdered on 16 June 2016. A Labour Party feminist, Jo campaigned for women's rights around the world. After graduating from the University of Cambridge in 1995, she became a political adviser for various MPs and then worked for Oxfam, the Maternity Mortality Campaign, Save the Children and the National Society for the Protection of Cruelty to Children. Jo Cox wanted to make the world a better place, a place of justice and peace.